Graphene-enhanced manganese dioxide functional ink infused with polyaniline for high-performance screen-printed micro supercapacitor - Shilpa Shetty; Mohammad Saquib; M Selvakumar; Hadi Firouzi; Ramakrishna Nayak (Materials Research Express, 2024)
In the world of miniature advancements in technology, a current champion has emerged: the micro supercapacitors. In order to fabricate these micro-supercapacitors, we have developed a promising and user-friendly approach for printing a conductive functional ink containing a ternary composite of manganese dioxide (MnO _2 ) nanoparticles, Graphene, and polyaniline (PANI) as a dopant. Screen-printing technique was employed to fabricate micro-supercapacitors using the nanocomposite conductive ink. The performance of the energy storage device was examined using flexible symmetric and asymmetric, with an aqueous 1 M KOH electrolyte. According to this strategy, the characterisation and electrochemical study results revealed that doping PANI into both symmetric and asymmetric devices significantly increased the material’s capacitive performance of areal capacitance 167 mFcm ^−2 for MnO _2 /Graphene/PANI-5 composite (MGP-5) and 292.5 mFcm ^−2 for asymmetric supercapacitor (ASSC) at 5 mVs ^−1 . Furthermore, the asymmetric supercapacitor displayed outstanding cyclic stability, retaining 93.6% of its capacitance after 10000 cycles. This underscores the possibility of incorporating polyaniline (PANI) into MnO _2 and graphene matrices as efficient blueprints for the development of superior electrode materials. The improvement represents a significant step forward, opening avenues for the future development of novel devices and their integration into top-of-the-line flexible energy storage systems.